UPAYA GURU UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI PROJECT BASED LEARNING DALAM PEMBELAJARAN IPS (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze teachers' efforts in developing students' critical thinking skills through the application of the Project Based Learning (PjBL) model in social studies learning. This study uses a qualitative approach with library research methods, by reviewing various scientific articles and other relevant sources. The results of the study indicate that students' critical thinking skills can be improved through the application of PjBL which emphasizes project-based activities, problem solving and active student involvement. Teachers' efforts in this regard include: 1) Planning project-based learning that is relevant to real life; 2) Encouraging students to be active in investigation and problem solving; 3) Creating an active, collaborative and conducive learning environment; 4) Providing appropriate guidance during the learning process; 5) Process and product-based assessment; and 6) Providing high-level questions. In addition, various studies have shown that PjBL is effective in improving students' analytical, evaluation and decision-making skills. However, the implementation of PjBL also faces challenges such as limited time, teacher readiness, and infrastructure. Therefore, it is necessary to improve teacher competence and support from various parties, to optimize the implementation of this model. Thus, it can be concluded that project-based learning is an effective learning model for developing students' critical thinking skills in social studies.